Optimizing Human Resource Management: Integrating Talent Development And Employee Welfare For Organizational Excellence - Sofyan, Hady; Asep Zulkifli Achmad; Helmita; Pasaribu, Donald Frensius (International Journal of Economics (IJEC), 2025)
This study analyzes the influence of talent development and employee welfare on organizational excellence in the context of human resource management in Indonesia. A quantitative approach was used with the partial least squares structural equation Modeling (PLS-SEM) analysis method using SmartPLS software. Data were collected through questionnaires administered to employees from various industrial sectors. The results of the analysis show that both talent development and employee welfare have positive and significant influences on organizational excellence, with coefficients of 0.421 and 0.367, respectively. Simultaneously, the two independent variables explained 64.2% of the variability in organizational excellence (R² = 0.642). This finding confirms that an effective HR management strategy must integrate employee competency development with improved work welfare to create a sustainable competitive advantage. This study’s managerial implications recommend the formulation of holistic, data-based, and long-term development-oriented HR policies